Predicting Taxpayers? Intentions of Adopting Electronic Tax-Filing (E-Filing) in Malaysia - Tan Teck Hong; Foo Yin-Fah (Journal of Accounting, Business and Management (JABM), 2012)
The objective of this paper is to examine the relative importance of adoption determinants, as defined by effort expectancy, performance expectancy, perceived risk, personal innovativeness, web self-efficacy and social influences in predicting intention to use e-filing in Malaysia. The results showed that the usefulness and ease of use of the e-filing system, social referents? opinion relating to e-filing and high control in the ability to use web site were statistically significant determinants of tax e-filing adoption. The Inland Revenue Board (IRB) should continue to raise the awareness of uninformed and inexperienced users to use e-filing through education, which would in turn push taxpayers to file their tax returns electronically.